Towards a new prudential framework for the insurance sector in Algeria - ALOUACHE , Sara; FEKARCHA , Sofiane; ATHAMNIA , raouf (Journal of Research in Finance and Accounting, 2026)
The objectives of this research are multiple; first, we will establish a solid theoretical basis using the academic literature to identify the risks that insurance companies are facing. Then, we will clarify that the concept of risk management is based on the three pillars of the European Solvency 2 directive, whether through the quantitative requirements of pillar 1, in terms of governance of pillar 2, or the expected reporting towards the regulator and the public of pillar 3. Finally, we will propose a framework leading to the establishment of the risk management system within the Algerian insurance companies.